Interaksi Guru dan Siswa: Analisis Mendalam terhadap Kurangnya Motivasi Belajar di Kelas Akibat Metode Pengajaran Tradisional - Andriani; Yusna; Yosi Ramadona; Eka Pratiwi Estiningtias; Anita Satriani (CV Putra Publisher, 2023)
The objective of this study is to assess the influence of conventional instructional approaches on students' motivation to engage in classroom learning. This study employs a qualitative approach, specifically utilizing a literature review methodology. The data was gathered from a variety of pertinent publications and journals. This research examines the interactions between professors and students within the framework of traditional teaching. The findings indicate that conventional instructional approaches, which frequently fail to actively involve students, have a substantial impact on diminishing students' willingness to acquire knowledge. The primary factors discovered were the absence of student engagement in the learning process and the absence of reciprocal contact between professors and students. Conversely, this study discovered that educators who employed a more engaging pedagogical method and linked the curriculum to real-life contexts effectively enhanced students' motivation to acquire knowledge